SUSTAINABILITY AND TAX INCENTIVES - Valentine Siagian; Nensy Dwi Putri Sinaga (Ekuitas: Jurnal Ekonomi dan Keuangan)
This study examines the link between sustainability practices and tax incentives for Indonesian firms by analyzing Bloomberg data from 2013 to 2022. It assesses sustainability through the Sustainability Growth Rate (SGR) and disclosures in the Environmental, Social, and Governance (ESG) domains, while tax incentives are measured by the Effective Tax Rate (ETR). A fixed-effects regression model controls firm-specific factors, revealing that a higher SGR significantly correlates with reduced tax liabilities. This study also suggests that firms with substantial sustainability growth are able to gain tax benefits. However, ESG disclosures alone do not significantly impact the ETR. Its robust sustainability practices have led to tax advantages rather than mere disclosure in Indonesia. Furthermore, this research contributes to the existing literature by highlighting the distinct impacts of various sustainability measures on financial outcomes, particularly in developing countries. They overview the importance of comprehensive sustainability strategies incorporating real growth in initiatives for achieving ethical and financial outcomes. This research also addresses critical insights for policymakers and business leaders in response to the emerging markets around developing countries.